A computational study of aromaticity and photophysical properties of unsymmetrical azatrioxa[8]circulenes; New Journal of Chemistry; Vol. 41, iss. 7 - Baryshnikov G. V. Gleb Vladimirovich; Valiev R. R. Rashid Rinatovich; Minaev B. F. Boris Filippovich; Agren H. Hans (2017, 2017)
Title screen